2020
DOI: 10.1038/s41467-020-16872-8
|View full text |Cite
|
Sign up to set email alerts
|

Diauxie and co-utilization of carbon sources can coexist during bacterial growth in nutritionally complex environments

Abstract: It is commonly thought that when multiple carbon sources are available, bacteria metabolize them either sequentially (diauxic growth) or simultaneously (co-utilization). However, this view is mainly based on analyses in relatively simple laboratory settings. Here we show that a heterotrophic marine bacterium, Pseudoalteromonas haloplanktis, can use both strategies simultaneously when multiple possible nutrients are provided in the same growth experiment. The order of nutrient uptake is partially determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 75 publications
2
49
0
Order By: Relevance
“…Many substrates belonging to the first cluster were depleted to their maximum potential before subsequent depletion of the second cluster began ( as a metabolic strategy is more common than previously thought when investigating the growth of heterotrophs in diverse, low concentration media (48,49). We observed that acetate, alanine, and glutamate likely provided the majority of carbon from SESOM for Paraburkholderia sp.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Many substrates belonging to the first cluster were depleted to their maximum potential before subsequent depletion of the second cluster began ( as a metabolic strategy is more common than previously thought when investigating the growth of heterotrophs in diverse, low concentration media (48,49). We observed that acetate, alanine, and glutamate likely provided the majority of carbon from SESOM for Paraburkholderia sp.…”
Section: Discussionmentioning
confidence: 65%
“…1N's biomass production in the first phase, lactate in the second, and reducing sugars coupled with valine in the final phase ( (10). Other observations of the co-existence of multiauxic and simultaneous substrate use tend to reinforce the idea that substrate selection is still based on affording the highest growth rate possible (31,49). Bacillus cereus is one other example of a fast-growing, r-selected organism that has been observed to selectively uptake substrates based on a mechanism outside of maximizing growth rate (31).…”
Section: Discussionmentioning
confidence: 94%
“…We performed all our expression trials in GG, a defined medium whose only carbon sources are D-gluconate and L-glutamate [ 3 ]. The uptake of substrates is hierarchical in Ph TAC125 [ 7 , 28 ] and specific amino acid combinations had to be formulated in the past to guarantee the optimal induction of another psychrophilic expression plasmid in this bacterium [ 5 ]. To understand if this kind of interference could be experienced also using pP79, we measured the achievable levels of β-galactosidase production when KrPL pP79- lacZ was grown in TYP, a complex medium containing yeast extract and bacto-tryptone.…”
Section: Resultsmentioning
confidence: 99%
“…Research on the depletion of PRC1 proteins EED or RING1B was followed by increased expression of differentiation markers in mouse ESCs [ 49 ]. Considering that ESCs have higher methylation rates than differentiated cells [ 50 ], such a global demethylation effect of CXCR4 inhibition would impose a critical defect on early embryonic development, including gastrulation, possibly contributing to prenatal death of CXCR4 knockout embryos. In addition, DNA methylation is a major spatiotemporal modulator of both pluripotency and differentiation during organogenesis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%